Buddhism and modernity: sources from nineteenth-century Japan - Klautau, Orion; Krämer, Hans Martin (University of Hawai'i Press, 2021)
Cover -- Halftitle -- Title -- Copyright -- Contents -- Buddhism and Modernity in Japan -- Part I Sectarian Reform -- Chapter 1 Questions and Answers from Beneath a Snowy Window (1876) -- Chapter 2 On Religious Revolution (1889) -- Chapter 3 "Fraternity of Puritan Buddhists: Our Manifesto" (1900) -- Chapter 4 "Discussing the Kanrenkai" (1897) -- Part II The Nation -- Chapter 1 On Protecting the Nation through Buddhism (1856) -- Chapter 2 "Upholding Faith in the Buddhadharma and Repaying the Nation" (1863) -- Chapter 3 "Lectures on the Three Articles of Instruction" (1873) -- Chapter 4 Laughing at Christianity (1869) -- Chapter 5 On the National Doctrine of Greater Japan (1882) -- Part III Science and Philosophy -- Chapter 1 A Buddhist Book of Genesis (1879) -- Chapter 2 "The Gist of Indian Philosophy" (1887) -- Chapter 3 Prolegomena to an Argument for the Revival of Buddhism (1887) -- Chapter 4 Discourse on Buddhist Unity (1901) -- Part IV Social Reform -- Chapter 1 "On Civilization" (1876) -- Chapter 2 "Publishing Goals of Hanseikai zasshi" (1887) and "Living the Pure Life" (1887) -- Chapter 3 "On the Relationship Between Man and Woman" (1888) -- Chapter 4 On Buddhist Marriage (1894) -- Chapter 5 The Problem of Faith (1904) -- Part V Japan and Asia -- Chapter 1 "A Plan to Protect the Dharma" (1874/1903) -- Chapter 2 "A Record of Niuzhuang" (1895) -- Chapter 3 "The Japanese People's Spirit" (1912) -- Chapter 4 A Travelogue in Tibet (1904) -- About the Editors and Contributors -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1800-1900; Modernität; Buddhismus; Japan